2015
DOI: 10.2196/jmir.3774
|View full text |Cite
|
Sign up to set email alerts
|

Using a 3D Virtual Supermarket to Measure Food Purchase Behavior: A Validation Study

Abstract: BackgroundThere is increasing recognition that supermarkets are an important environment for health-promoting interventions such as fiscal food policies or front-of-pack nutrition labeling. However, due to the complexities of undertaking such research in the real world, well-designed randomized controlled trials on these kinds of interventions are lacking. The Virtual Supermarket is a 3-dimensional computerized research environment designed to enable experimental studies in a supermarket setting without the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 34 publications
(40 reference statements)
5
82
1
1
Order By: Relevance
“…As obesity has now become an epidemic, there is a clear need for an easy‐to‐use tool for exploring the differences between people who suffer from the same problem and shopping in the supermarket is a good scenario in which to examine the issue. Due to the complexities of undertaking research in a real supermarket, there are studies that used a virtual supermarket environment (Waterlander, Jiang, steenhuis, & Ni Mhurchu, ) to investigate the shopping behavior of obese individuals. In this study, a questionnaire was developed which could be used to learn more about the participant's supermarket shopping experience and to investigate both the individual's shopping habits and EF while shopping.…”
Section: Discussionmentioning
confidence: 99%
“…As obesity has now become an epidemic, there is a clear need for an easy‐to‐use tool for exploring the differences between people who suffer from the same problem and shopping in the supermarket is a good scenario in which to examine the issue. Due to the complexities of undertaking research in a real supermarket, there are studies that used a virtual supermarket environment (Waterlander, Jiang, steenhuis, & Ni Mhurchu, ) to investigate the shopping behavior of obese individuals. In this study, a questionnaire was developed which could be used to learn more about the participant's supermarket shopping experience and to investigate both the individual's shopping habits and EF while shopping.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Waterlander et al [31] recently showed that shopping patterns in a virtual supermarket were comparable to those in real life and conclude that virtual supermarkets are a valid tool to measure food purchasing behavior. It is worth noting that authors stressed that it is important to improve the functionality of some food categories, in particular fruits, vegetables and dairy.…”
Section: Comparisons Between Real and Virtual Supermarketsmentioning
confidence: 94%
“…It is worth noting that apart from Waterlander et al [31,34], none of these research integrated fresh food and more specifically FaVs. Only [33] used some fresh FaVs in their webbased 3D supermarket but without offering any variability (a single 3D model was a used for each type of FaV).…”
Section: Comparisons Between Real and Virtual Supermarketsmentioning
confidence: 99%
“…It can also be used to efficiently deliver realistic food cues to elicit craving (at least as indexed by self-report and salivation) just like actual food does (Ledoux et al, 2013; though see also . Intriguingly, virtual stores can elicit similar consumer choice of food products such as milk and cookies as those that have been documented in a physical store (van Herpen et al, 2016; see also Waterlander et al, 2015), and have been used to examine purchases of alcoholic drinks, such as beer (Bigné et al, 2016).…”
Section: Introductionmentioning
confidence: 99%